2010
DOI: 10.2174/1875038901003010074
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemistry of Cyclodextrin Inclusion Complexes of Pharmaceutical Compounds

Abstract: Electrochemistry of cyclodextrins (CDs) and cyclodextrin inclusion complexes with different pharmaceutical compounds is reviewed. The article highlights some electrochemical investigations of the CD-drugs interactions in solution. Cyclodextrin modified electrodes and their applications as electrochemical sensors in pharmaceutical analysis based on the self-assembly of CD derivatives on metal electrodes and nanoparticles, and cyclodextrin-modified multiwalled carbon nanotubes are also discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 116 publications
(110 reference statements)
0
8
0
Order By: Relevance
“…This plot shows that the aqueous solubility of the drug increases linearly as a function of α -cyclodextrin concentration. It is clearly observed that the solubility diagram of Tamoxifen citrate in the presence of α -cyclodextrin can be classified as the A L type 10 . The linear host guest correlation with slope of less than 1 suggested the formation of a 1:1 complex (Tamoxifen citrate: α -cyclodextrin) with respect to α -CD concentrations.…”
Section: Phase Solubility Studymentioning
confidence: 99%
“…This plot shows that the aqueous solubility of the drug increases linearly as a function of α -cyclodextrin concentration. It is clearly observed that the solubility diagram of Tamoxifen citrate in the presence of α -cyclodextrin can be classified as the A L type 10 . The linear host guest correlation with slope of less than 1 suggested the formation of a 1:1 complex (Tamoxifen citrate: α -cyclodextrin) with respect to α -CD concentrations.…”
Section: Phase Solubility Studymentioning
confidence: 99%
“…The ability of inclusion complex formation is mainly due to the thermodynamics of the process [9] and possible non-covalent interactions (NCI) between the ligand and the CD cavity [10]. Thermodynamically, the inclusion process is guided by the inclusion constant (𝐾 𝑖 ), entropy (∆𝑆), enthalpy (∆𝐻), and Gibbs free energy of reaction (∆𝐺) [11,12,13], in addition to the non-covalent interactions between the ligand and the cavity [10,14].…”
Section: Introductionmentioning
confidence: 99%
“…Cyclodextrins (CDs) are toroidal-shaped, biocompatible, relatively non-toxic, cyclic oligomers [ 16 ]. In aqueous solutions, CDs can incorporate geometrically and polarity-compatible target compounds to improve their stability [ 17 ], increase their solubility [ 18 ], and enhance their bioavailability [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…In aqueous solutions, CDs can incorporate geometrically and polarity-compatible target compounds to improve their stability [ 17 ], increase their solubility [ 18 ], and enhance their bioavailability [ 19 ]. This increases the applicability of CDs in many fields, including pharmaceutics [ 16 , 20 ], cosmetics [ 17 ], and food technology [ 21 , 22 ]. Therefore, many researchers have deemed CDs as potential specific drug carriers or nano-inclusion agents with the ability to reduce the toxicity of target compounds, after numerous modifications [ 23 ].…”
Section: Introductionmentioning
confidence: 99%